2014
DOI: 10.1111/ede.12074
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal transfer of the msp130 gene supported the evolution of metazoan biomineralization

Abstract: It is widely accepted that biomineralized structures appeared independently in many metazoan clades during the Cambrian. How this occurred, and whether it involved the parallel co-option of a common set of biochemical and developmental pathways (i.e., a shared biomineralization "toolkit"), are questions that remain unanswered. Here, I provide evidence that horizontal gene transfer supported the evolution of biomineralization in some metazoans. I show that Msp130 proteins, first described as proteins expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 51 publications
2
29
1
Order By: Relevance
“…Additionally, we did not find an msp130 gene in the whole genome sequence of the biomineralising cnidarian, Acropora digitifera, in addition to the other supposedly non-biomineralising non-bilaterian taxa surveyed by Ettensohn (2014). Thus, this cnidarian data does not resolve whether the msp130 genes in bilaterians stem from a HGT event early in bilaterian evolution, before the origin of protostomes and deuterostomes, or instead the gene was present at the origin of animals and has been secondarily lost, not only from some bilaterian lineages, but also several non-bilaterian lineages.…”
Section: Conserved Gene Structure Across Bilateriacontrasting
confidence: 66%
See 2 more Smart Citations
“…Additionally, we did not find an msp130 gene in the whole genome sequence of the biomineralising cnidarian, Acropora digitifera, in addition to the other supposedly non-biomineralising non-bilaterian taxa surveyed by Ettensohn (2014). Thus, this cnidarian data does not resolve whether the msp130 genes in bilaterians stem from a HGT event early in bilaterian evolution, before the origin of protostomes and deuterostomes, or instead the gene was present at the origin of animals and has been secondarily lost, not only from some bilaterian lineages, but also several non-bilaterian lineages.…”
Section: Conserved Gene Structure Across Bilateriacontrasting
confidence: 66%
“…We used the full list of MSP130 proteins provided by Ettensohn (2014) to generate neighbor-joining and maximum likelihood trees (Fig. 1).…”
Section: Annelids Possess Msp130mentioning
confidence: 99%
See 1 more Smart Citation
“…proteins are also expressed selectively in biomineralizing tissues in other marine phyla, pointing to a conserved role (Ettensohn, 2014;Szabó & Ferrier, 2015 Regulatory inputs into PMC effector genes (S. purpuratus). More than 400 effector genes are expressed selectively by PMCs (Rafiq et al, 2014), of which only a small subset is shown here.…”
Section: Activation Of Skeletogenic Effector Genesmentioning
confidence: 99%
“…In these families, changes in cis-regulatory sequences appear to enable the high expression of these genes in mantle cells. Another evolutionary mode of shell matrix proteins could be horizontal gene transfer, although horizontal gene transfer has not been reported in molluscs, there is evidence that this process supports biomineralisation in other taxa , Ettensohn 2014). …”
Section: The Molecular Basis and Modes Of Shell Matrix Protein Evolutionmentioning
confidence: 99%